2019
DOI: 10.3390/jcm8091301
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Challenges in Metabolic Syndrome

Abstract: Metabolic Syndrome (MetS) is a combination of risk factors for the development of cardiovascular disease (CVD) and type 2 diabetes. Different diagnostic criteria were proposed, but a consensus was reached in 2009 based on values of waist circumference, blood pressure, fasting glycemia, triglycerides, and high-density lipoprotein (HDL)-cholesterol levels. The main underlying etiologic factor is insulin resistance. The quality and quantity of individual macronutrients have an influence on the development and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 73 publications
0
58
1
4
Order By: Relevance
“…A recent review showed that moderate weight loss (between 5 and 10% of one’s initial body weight) resulted in a significant reduction in glucose, triglycerides, and total cholesterol and improved insulin sensitivity by between 30 and 60%, which are effects greater than those seen with insulin-sensitizing drugs [ 66 ]. In the CD group, a significant reduction in fasting plasma glucose, insulin resistance that was assessed using the HOMA-IR index, and total cholesterol and LDL-C was observed, while the level of HbA1c remained almost the same.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review showed that moderate weight loss (between 5 and 10% of one’s initial body weight) resulted in a significant reduction in glucose, triglycerides, and total cholesterol and improved insulin sensitivity by between 30 and 60%, which are effects greater than those seen with insulin-sensitizing drugs [ 66 ]. In the CD group, a significant reduction in fasting plasma glucose, insulin resistance that was assessed using the HOMA-IR index, and total cholesterol and LDL-C was observed, while the level of HbA1c remained almost the same.…”
Section: Discussionmentioning
confidence: 99%
“…The increased intake of carbohydrates with a high glycemic Index (GI) is known to directly induce insulin resistance and contribute to the development of type 2 diabetes in MetS patients. On the other hand, diets with a low GI, high in fiber, increase the feeling of satiety and reduce insulin resistance and the risk of type 2 diabetes [29]. It is also suggested that people's health may be influenced by the local environment.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term adherence to a healthy lifestyle is the key of lifestyle management for patients with metabolic syndrome. Several dietary patterns have been proved to ameliorate insulin resistance and MetS including Mediterranean-style, dietary approaches to stop hypertension (DASH), low-carbohydrate, and low-fat diets [ 37 ]. Neurohormonal activation is one of the mechanisms involved in MetS.…”
Section: Management Of the Metabolic Syndrome In Preventing Heart Faimentioning
confidence: 99%